Improving plantain (Musa spp. AAB) yields on smallholder farms in West and Central Africa - Norgrove, L.; Hauser, S. (Springer, 2014)
Plantain is an important staple in West and Central Africa, where it is predominantly grown by smallholder farmers. On-farm data are rare but yields are considered to be low. We collated actual yields in the region, reviewed regional plantain research published from 1976 to 2013, then estimated what yields would be attainable on smallholder farms if the proven, best-fit innovations were adopted. Mean actual yields reported ranged from 2.9 to 8.9 Mg ha?1 with a mean of 5.7 Mg ha?1 for False horn plantain and 4.5 to 10.2 Mg ha?1 with a mean of 7.8 Mg ha?1 for French plantain. Experiments found dealt with: cultural practices, particularly intercropping; abiotic factors such as fertiliser, mulch application and irrigation; biotic factors, predominantly sucker sanitation methods, but including three controlled yield loss studies on nematodes and black sigatoka; landrace comparisons and the introduction of improved cultivars, predominantly those exhibiting black sigatoka-tolerance. We conclude that intercropping should be retained according to farmer preference as there was no evidence of yield reductions for plantain. Boiling water treatment of suckers should be universally recommended. Inputs, whether mulch or K fertiliser up to 300 kg ha?1, should be applied as both reduced plant losses and increased bunch mass. With the highest yielding local landrace type, on-farm yields could be increased from 7.8 Mg ha?1 to 35.5 Mg ha?1 with purchased inputs or to 23.7 Mg ha?1 without purchased inputs.